Incapacidades físicas por hanseníase no período de 2001 a 2011 no estado da Paraíba - Uchôa, Rosa Emília Malta Nascimento (2014)
Leprosy is a chronic granulomatous disease, from infection caused by Mycobacterium leprae. The bacillus has the ability to infect large numbers of individuals, however few sick that these properties are not only a function of its intrinsic characteristics but depend mainly on their relationship with the host and degree of endemicity of the environment, among other aspects. Since leprosy is really about is a public health problem, with high incidence not only in Brazil but worldwide, which causes physical harm and hence functional impairment, it is valid to conduct studies to identify the prevalence of disabilities and disabilitie, as well as the areas of highest concentration of these in order to target more specific actions by health professionals. Objectives: To identify the profile of leprosy cases diagnosed with physical disabilities in Paraíba, between the years 2001-2011 ; To determine the prevalence of physical disability in leprosy patients in the period 2001 to 2011 in the state of Paraíba; Identify spatial patterns of occurrence of leprosy by physical disabilities in the state of Paraíba , between the years 2001-2011. Methodology: We conducted an epidemiological study of temporal, retrospective and documentary based series, from the leprosy cases reported by Sinan in the state of Paraíba in the period 2001-2011. Selected for the study were all new cases of leprosy, who had physical disability I and / or II at diagnosis, registered in the period from 2001 to 2011, diagnosed in the state Paraíba, corresponding to a total of 3,408 cases detected in the period. For data analysis, absolute and percentage distributions (descriptive statistical techniques) were obtained, and inferential statistical techniques. The approved by the Center for Health Sciences/UFPB Research Ethics Committee, as subproject of a larger research entitled "Epidemiological profile of leprosy patients in Paraíba: 2001 - 2011" project, with the number n° 203 485, CAAE 11076312.1 .0000.5188. Results: This study showed that of the 3,408 cases of leprosy who had some degree of physical disability ( I or II ) , 2969 refer to the GIF I and 439 to GIF II . We found an overall prevalence of 65,2% of disability installed at diagnosis with media endemicity parameters for cases with GIF II ( 8,4% ) . For all variables studied were no statistically significant differences between grades I and II disability. Concerning the spatial distribution of leprosy in Paraíba results show high detection rates in the regions of CajazeirasGuarabira Hope Itaporanga ,João Pessoa and Eastern Seridó . Only micro Western Seridó had no reported cases of physical disability. Conclusion: Considering the current state of health in Paraíba studied and reviewed the findings of the study suggest that there is a long period to be followed in municipal, state and federal health , what concerning the control of leprosy , however the identification of vulnerable population , the use of GIS techniques and commitment of professionals are notably large power tools to change this situation.